The effects of the Promove-Casais program on conjugality, parenting, mental health, and child behavior - de Lima Ferraz, Flaviane Izidro Alves; Bolsoni-Silva, Alessandra Turini [UNESP] (Universidad Catolica de Uruguay, 2023)
This study describes the effects of the Promove-Casais program on marital relationships, parenting, child behavior, and mental health. Nine couples were randomly assigned to two groups: five to the experimental group (EG) and four to the control group (CG). The participants completed the instruments measuring this study's variables of interest. The results indicate the intervention was effective because, after the intervention, the experimental group more frequently experienced positive relationships (improved communication, affection, and self-control), positive parent-child interactions, and improved marital satisfaction and children's social skills, while negative marital relationships, negative parent-child interactions, and problem behaviors subsided; these results remained in the follow-up. On the other hand, the CG experienced no such changes. The conclusion is that Promove-Casais can be implemented to prevent and remediate interactional problems within the family, promoting improved quality of life and mental health.
Efectos del programa Promove-Casais para la conyugalidad, la paternidad, la salud mental y el comportamiento de los niños
Efeitos do programa Promove-Casais para a conjugalidade, parentalidade, saúde mental e comportamentos infantis
Keywords: behavior problems; Behavioral Analytic Therapy; marital relationship; mental health; parent-child relationships; social skills